PERLINDUNGAN HUKUM TERHADAP PEMEGANG KARTU E-MONEY SEBAGAI ALAT PEMBAYARAN DALAM TRANSAKSI KOMERSIAL - Ni Nyoman Anita Candrawati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
One means of electronic or non-cash payments are by using electronic money card (e-money). Value of money is stored electronically and issued on the basis of the value of money paid to the holders of the provider. The money is used as a means of payment, but not the deposit as stipulated in the Banking Law, so it is not guaranteed by Saving Guarantee Institution (LPS).   There are two issues that were examined in this study, namely: the arrangements for electronic money card holders in e-money transactions and legal protection for the cardholder to perform e-money transactions. The research is a normative legal research using law and conceptual approach. Based on the results of studies conducted on the issue, the legal regulation of the form of electronic    money    stipulated    in    Bank    Indonesia    Regulation    Number 11/12/PBI/2009   on   Electronic   Money,   and   through   standard   agreements governed by the provider, such as terms and conditions of the card holder. Legal protection for the cardholder is required to ensure the equality of the provider and the card holder, including legal protection against the misuse of e-money card that can be detrimental to the holder, through preventive and repressive legal protection.